Revolutionary Activities of Indian Sufis and Sheikh Sirhindi regarding Social Reforms and Interfaith Harmony: Analytical Study of Imam Rabbani’s Letters - Baig, Hassan; Majeed, Hafiza Hafsa (sourcecoder, 2024)
Today, many Muslim societies suffer from such insecurity, fear, terror, anarchy, bloodshed, and murder. One of the main reasons for this is that nature has not provided the right opportunities and environment for human beings to satisfy these tender human emotions. Although we are floating with the changing trends of the world like a reed floating in a raging storm of a river without any destination. While on the other hand, Sufis and Sufism have an important and wonderful role for inducing those tender feelings in human beings that creates such a structure that the people of the society are inspired to promote Interfaith harmony between religions and reform the society are assigned In fact, Shaykh Mujaddid al-Thani, and his family, with his reformist teachings, not only reformed the useless system that had been created in the society, but also changed the illegal and false thinking that was prevalent in Sufism. It has revived the doctrine and spirit of Sufism and the authenticity of beliefs in Islam, which has inspired deep reform aspects to promote Interfaith dialogue, peace, and harmony between religions in the society and to address the demand for the progressive rights of humanity in Sufism.